Tekke Mûsikîmizde Toplu Evrâd-ı Şerîf Okuma Geleneğine Bir Örnek: Rifâî Evrâd-ı Şerîfi - (:unkn) unknown (My University, 2018)
Tekke mûsikîmizde yüzyıllardır her tarikat âyininin başında yer alan ve dervişlerin zikre rûhî olarak hazır olmalarına yardımcı olan besteli evrâd-ı şerîfler günümüzde çok az bilinen ve henüz çoğu tespit edilememiş bir dinî musiki formudur. Her tarikatın pîri tarafından tertîb edilmiş, bazı sûre, salavât ve duâlardan müteşekkil evrâdlar, belirli bir müzikal yapıya sahiptir ve her tarikatın zikir günü olarak kabul edilen hafta gününde zikirden önce ve vakit namazının ardından toplu olarak okunmaktadır. Dini mûsikîmizdeki bu gele-nek çeşitli sebeplerle kesintiye uğramıştır. 1950-60'lı yıllardan sonra dergâh-lardaki yüksek mûsikî zevkini tatmış olan ehil zâtların kişisel gayretleri ile son-raki nesillere aktarılarak günümüze ulaşmıştır. Toplu evrâd-ı şerîf okuma ge-leneği üzerine yaptığımız bu çalışmada öncelikle evrâd literatürü ve tekke kültürümüzdeki yeri hakkında bilgi verdik ve Rifâî Evrâdı'nın metin olarak ana hatlarını sunduk. Çalışmamızın müzikal kısmını İstanbul ve Üsküp'te okunan Rifâî evrâdları ile sınırlandırdık. İstanbul ekolü için Cumhuriyet döneminin son Rifâî şeyhlerinden olan Ken'ân Rifâî'nin faaliyete geçirdiği ve İstanbul'daki Rifâî usül ve erkânının en yetkin kişiler aracılığı ile icrâ edildiği Ümmü Ken'ân Dergâhı'ndan bugüne çok değerli mûsikîşinaslarımız tarafından nesilden nesi-le aktarılan icrâ tavrını esas aldık. Üsküp ekolü için ise Üsküp Rifâî Âsitâne-si'nden gelen gelenek ile 1956 senesinde Türkiye'ye göç eden âsitânenin 6. şeyhi Mustafa Haznedar Baba ve oğlu Râik Haznedar tarafından günümüze ulaşmış icrâ tavrını esas aldık. Her iki coğrafyada okunan evrâd icrâslarını notaya aldık ve müzikal analizlerini yaptık. Daha sonra beste olarak ne gibi etkileşimleri olduğunun izini sürmeye çalıştık. Sonuç olarak her iki ekolün benzerlik ve farklılıklarını incelediğimizde her iki icrânın da kadîm İstanbul Tekke Mûsikîsi'nden doğduğu ve beslendiği düşüncesi ortaya çıkmaktadır.

Composed mass-invocations "evrad-ı sharif" is a religious music form that is hardly known today and mostly undiscovered, which used to take place at the beginning of all dervish order rituals and helped the dervishes prepare for the invocations ("zikr") spiritually. These mass invocations, arranged by each order's sage ("pir") and consisting of certain surahs, salawat and prayers, had a specific musi-cal structure and were chanted collectively on the day of the week that was acknowledged as the "zikr" day for that order, right before the "zikr" and after prayer time ("salaah"). For a variety of reasons, this tradition in our religious music was interrupted. After 1950-60s, with personal ef-forts of competent personages who have experienced this high musical pleasure in dervish lodges, it was passed on to later generations, all the way to present day. In this study we have conducted on the tradition of mass-chanting of “evrad-ı sharif”, first we presented the data about the literature of evrad and its place within our tradition of lodges and then outlined Rifai's Evrad as a text. We limited the musical aspect of our study with Rifai evrads chanted in İstanbul and Skopje only. For Istan-bul school, we based our study on the manner of musical execution of Ümmü Ken'an Lodge, which was founded by one of the last Rifai sages of the Republic era, Ken'an Rifai and saw the performances of the most competent personages in Rifai methods and manners, and this manner was passed down through generations to this day by esteemed music lovers. For Skopje school, on the other hand, we based our study on the manner of musical execution that was passed down to this day by the 6th sage of the "Asitane" (the main lodge of a given dervish order in the area) of Skopje Rifai Order, Mustafa Haznedar Baba, who migrated to Turkey in 1956, and his son Raik Haznedar. We notated evrad per-formances from both locations and conducted musical analysis. Next, we tried to trace any possible compositional interactions between the two. As a result, after studying the similarities and differences of these two schools, a conclusion about both manners being born and nurtured from the ancient İstanbul Lodge Music can be drawn.
An Example of the Traditional Mass-Invocations Evrad-i Sharif in Islamic Lodge Music; Rifai's Evrad-i Sharif
Keywords: Din Bilimi